Mediating urban transition through rural tourism. (March 2019) - Li, Yiping; Zhang, Heqing; Zhang, Dian; Abrahams, Richard
Highlights: China's rural places and peoples are created and consumed through tourism. Cultural processes at home inform the urban tourists about the rural areas. The countryside has become a place of cultural meaning to urban tourists. Places of rural, ethnic minorities are on-going productions of social relations. Tourism is a force of change that interacts and becomes part of new realities. Abstract: This study examines China's urban–rural transition in the process of development and change. Regarding tourism as a discourse of difference, it focuses on a rural ethnic community, Jiabang, in Southwest China. It aims to highlight the role of tourism in providing a stimulus for the creation of a local group identity that subverts wider discourses of rural areas. With the goal of understanding how toured places are imagined, presented and consumed, this study utilises mixed data sources collected from tourism promotional materials and ethnographic fieldwork. The findings suggest that the forces behind the touristic place creation and consumption are both integral to and the result of the changing attitudes and perceptions of people and places in contemporary China.